Isolation and Characterization of Nocardiodies nitrophenolicus Capable for Degradation of P-Nitrophenol - Patel, Priti; Bhatt, Shreyas (Asian Journal of Biological and Life Sciences, 2015)
P-Nitrophenol is the potent contaminant in the environment. We have isolated and characterize the Nocardiodies nitrophenolicus strain use for degradation of P-Nitrophenol. Greatest degradation of PNP was observed at 35°C and under slightly alkaline pH (pH 7–9) conditions. Effective degradation rates slowed as the concentration of PNP was increased. Addition of glucose from 0.1% to 0.5% generally enhanced the degradation of PNP at high concentration (325 mg/l) although acidification as a result of glucose metabolism had a negative effect on PNP depletion. On the basis of 16S rRNA gene sequencing the bacterium is a species of Nocardiodies, closely related to Nocardiodies nitrophenolicus.
Keywords: 16S r-RNA sequencing; Degradation; Glucose; Nocardiodies nitrophenolicus; P-Nitrophenol